Role of Neuron and Glia in Alzheimer’s Disease and Associated Vascular Dysfunction - Bandyopadhyay, Sanghamitra (Frontiers in Aging Neuroscience, 2021)
Amyloidogenicity and vascular dysfunction are key players in the pathogenesis of Alzheimer’s disease (AD), involving dysregulated cellular interactions. An intricate balance between neurons, astrocytes, microglia, oligodendrocytes as well as vascular cells sustains the normal neuronal circuits. Conversely, cerebrovascular diseases overlap neuropathologically with AD, and glial dyshomeostasis promotes AD-associated neurodegenerative cascade. While pathological hallmarks of AD primarily include amyloid-β (Aβ) plaques and neurofibrillary tangles, microvascular disorders, altered cerebral blood flow and blood-brain barrier permeability induce neuronal loss and synaptic atrophy. Accordingly, microglia-mediated inflammation and astrogliosis disrupt the homeostasis of neuro-vascular unit and stimulate infiltration of circulating leukocytes into the brain. Large scale genetic and epidemiological studies demonstrate a critical role of cellular crosstalk for altered immune response, metabolism and vasculature in AD. The glia associated genetic risk factors include APOE, TREM2, CD33, PGRN, CR1 and NLRP3, which correlate with the deposition and altered phagocytosis of Aβ. Moreover, aging-dependent down-regulation of astrocyte and microglial Aβ-degrading enzymes limits the neurotrophic and neurogenic role of glial cells and inhibits lysosomal degradation and clearance of Aβ. Microglial cells secrete IGF-1, and neurons show a reduced responsiveness to the neurotrophic IGF-1R/IRS-2/PI3K signaling pathway, generating amyloidogenic and vascular dyshomeostasis in AD. Glial signals connect to neural stem cells, and a shift in glial phenotype over the AD trajectory even affects adult neurogenesis and the neurovascular niche. Overall, the current review informs the interaction of neuronal and glial cell types in AD pathogenesis and its critical association with cerebrovascular dysfunction.